STEREOTYPE THREAT: EFFECTS ON WOMEN DRIVING SELF EVALUATION MODERATED BY MENSTRUAL CYCLE - ERDOĞAN, Tolga; KÖSEOĞLU, Beyza; CZUKOR, Gergely (Atlas Journal, 2021)
This study investigated the moderating role of menstrual cycle in the relationship between gender stereotype salience and women’s self-perceptions in terms of driving self-esteem and, stress and tension among 130 Turkish females. The study used a 2 (Stereotype salience: experimental or control) X 2 (Menstruation cycle: Menstruation period, or absence of period) experimental design. In phase 1, participants completed a survey to forecast the dates of their coming menstrual period. In Phase 2, based on the anticipated menstruation dates, participants were assigned randomly into experimental or control condition. In the experimental condition, participants were exposed to a gender laden car advertisement associating males with a sport car and females with a smaller, round-shaped automobile. In the control condition, the participants were not exposed to any gender and driving information. The results indicated that stereotype type salience single-handedly did not have a negative impact. However, stereotype salience and menstrual cycle had a significant interaction on both outcome variables. For participants who reported having a menstrual period, in the stereotype salience condition, stress and tension was higher, and self-esteem was lower as compared to the control condition. Both effects approached a large effect size. The effects were no significant for those without their period. The study draws attention to the important role of menstrual cycle as a magnifier of stereotype threat effects among female drivers.